The Cusco ceque system as shown in the Exsul immeritus Blas Valera populo suo. (2nd January 2016) - Bauer, Brian S.
Abstract : In this article I discuss a recently discovered drawing of the Cusco ceque system. A previous study of the drawing suggests that it is an inaccurate reproduction of the system. In contrast, I propose that the drawing is accurate and organizes information on the system in ways not considered by scholars before. While the accuracy of the drawing is confirmed, the question of authorship remains open.